Determining K-coefficients value in payment for Environmental Services Program of Bu NDor’s Community Forest, Dak Nong province, Vietnam - Bao, Ho Dinh (2016)
Payment for Environmental Services (PES) has been implemented in Vietnam to prove the buyers about the services that they benefit. The environmental values in PES are calculated via a K-coefficient which present different type of forest characteristics of a particular area. The main objective of this study was to determine the K-coefficient value that is used to adjust the payment in the payment for environmental services program within Bu N’Dor community forest. The research used SPOT-5 satellite image that was captured in 2012 to classify forest status. One hundred and four sample plots were collected in the field corresponded with three forest status which were rich, average, and poor forest. To classify forest status based on satellite image, Envi 4.7 software was used as a core software that interpreted forest condition according to digital value of the pixels in the image. The Kcoefficient (K1) was assigned based on forest status and it vary from 0.90 to 1.00. The second K-coefficient (K2) is based on the essential soil erosion. The Revised Universal Soil Loss Equation was used to calculate the essential soil erosion in the area. The essential soil erosion value was classified to eight classes according to Vietnam standard in 1995 (TCVN 5299 – 1995). Essential soil erosion K-coefficient (K2) map was then created corresponded with soil erosion level. It value varies from 0.75 to 1.00. The third K-coefficient was defined by the forest managed purposes (K3). Extracting the forest managed purposes map and assigning the K value based on production forest (K=0.90) or protection (K=0.95) forest. The fourth K-coefficient map (K4) was defined by the difficulty in forest protection. Four groups who were responsible for forest protection were interviewed, they divided the forest into three levels from average to very difficult in term of forest protection on a map that was provided. These maps were scanned, digitized, and assigned the K value (0.90 – 1.00) to create K4 map. The general K-coefficient map was built by overlay four K-coefficient maps which are K1, K2, K3 and K4 following the PES policy. The general K values are from 0.73 to 0.95. From that map, the value of environmental services that the community forest served was calculated by multiply with the price per hectare (USD 20). The total environmental services value is USD 15,729.60. The essential soil erosion Kcoefficient (K2) was calculated by some factors that related to forest conditions so that could replace K1 to calculate the new K-coefficient and the value of the community forest was reduced to USD 13,170.24. In conclusion, the K-coefficient map that reflected the different on providing environmental services of different areas could be used to calculate the environmental value of the community forest and contribute to the payment method of PES program in Vietnam.